1982
DOI: 10.1128/aem.43.1.104-109.1982
|View full text |Cite
|
Sign up to set email alerts
|

Production and properties of cyanobacterial endotoxins

Abstract: Lipopolysaccharides (LPS) were isolated from four species of cyanobacteria (Anabaena flos-aquae UTEX 1444. A. cylindrica, Oscillatoria tenuis, and O. brevis) frequently occurring in drinking-water supplies. The cyanobacterial LPS contained glucose, xylose, mannose, and rhamnose, but differed from the LPS derived from most gram-negative bacteria because of the variable presence of 2-keto-3-deoxyoctonate, heptose, galactose, and glucosamine. Cyanobacterial lipid A is characterized by long-chain saturated an unsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…This is the first experimental evidence that axenic cyanobacteria have not caused allergenic effects on albino guinea pigs. Keleti and Sykora (1982) emphasized that the allergenic effect is more likely caused by lipo polysaccharides of cell walls, than the toxin content. Our experiments strengthen this statement but implicate the lipopolysaccharides of contaminant bacterial flora rather than cyanobacterial cell walls.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first experimental evidence that axenic cyanobacteria have not caused allergenic effects on albino guinea pigs. Keleti and Sykora (1982) emphasized that the allergenic effect is more likely caused by lipo polysaccharides of cell walls, than the toxin content. Our experiments strengthen this statement but implicate the lipopolysaccharides of contaminant bacterial flora rather than cyanobacterial cell walls.…”
Section: Resultsmentioning
confidence: 99%
“…Cyanobacterial LPS have previously been shown to have lower toxicity in vivo than LPS from highly toxic bacteria such as Salmonella sp. that are often lethal for mice and highly pyrogenic in experiments with rabbits (Keleti et al, 1979;Weckesser et al, 1979;Schmidt et al, 1980;Keleti and Sykora, 1982;Raziuddin et al, 1983). Although acute endotoxin toxicities of cyanobacterial LPS may be lower than those Salmonella, several recent reports describe the modulatory effects of LPS on the metabolism and toxicities of other compounds (such as cyanotoxin microcystin) in aquatic organisms (Best et al, 2001(Best et al, , 2002(Best et al, , 2003Pietsch et al, 2001;Lindsay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacteria produce LPS as an important constituent of the cell wall. Cyanobacterial LPS differs from that of most other bacteria in lacking phosphate in the lipid A core (Keleti and Sykora 1982). In animal experiments cyanobacterial LPS is about 10 times less toxic than enterobacterial LPS (Codd 1984).…”
Section: Lipopolysaccharide Endotoxinmentioning
confidence: 93%
“…Reports of the effect of the injection of endotoxins in mice give conflicting results. Some studies have shown no effect (Weise et al 1970;Keleti et al 1979) while other have demonstrated lethal effects including positive Schwartzman reactions (Keleti et al 1979;Keleti and Sykora 1982).…”
Section: Lipopolysaccharide Endotoxinmentioning
confidence: 99%